Araucaria araucana Forests in Argentina: Exploring Floristic and Ecological Variability Along a West-East Transect - Martinez Carretero, Eduardo Enrique (2024)
In Argentina, the Araucaria araucana forest occupies a vast area in the Northwest of Patagonia, following a pronounced gradient of increasing xericity from west to east over a short distance. These forests have been the subject of detailed studies due to their uniqueness and ecological relevance. In this context, an exhaustive investigation was carried out to understand the diversity and structure of these ecosystems. The objective was to study the floristic and ecological differences in humid and xeric areas along a west-east transect where A. araucana is distributed. Floristic surveys, geomorphological analyses, and bioclimatic data were examined. In Argentina, A. araucana integrates two distinct forest types: mesic and xeric. The xeric A. araucana forest constitutes a forest with floristic, genetic, geomorphological, and bioclimatic identity. The results highlight the importance of understanding the local variability of these ecosystems for the design of effective conservation strategies. Furthermore, they highlight the need for further research into the ecology and dynamics of these forests, especially in the context of climate change and human activities.